Spiritual formation in emerging adulthood : a practical theology for college and young adult ministry - Setran, David P. (Grand Rapids, Michigan : Baker Academic, 2013)
"The shift from adolescence to adulthood, a recently identified stage of life called 'emerging adulthood,' covers an increasing span of years in today's culture (roughly ages 18-30) due to later marriages and extended education. During this prolonged stage of exploration and self-definition, many young adults drift away from the church. Here two authors--both veteran teachers who are experienced in young adult and campus ministry--address this new and urgent field of study, offering a Christian perspective on what it means to be spiritually formed into adulthood. They provide a 'practical theology' for emerging adult ministry and offer insight into the key developmental issues of this stage of life, including identity, intimacy and sexuality, morality, church involvement, spiritual formation, vocation, and mentoring. The book bridges the gap between academic and popular literature on emerging adulthood and offers concrete ways to facilitate spiritual formation among emerging adults" -- Publisher description.
Faith: the emerging adult landscape -- Spiritual formation: reversing moralistic therapeutic deism -- Identity: internalization, refusal, and engagement -- Church: forming an ecclesiological vision -- Vocation: purpose and providence -- Morality: training the dispositions of the soul -- Sexuality: forming a sexual ethic -- Relationships: pitfalls and pathways -- Mentoring: past, present, and future.
Includes bibliographical references and index.
Keywords: Spiritual formation; Young adults -- Religious life; Church work with young adults; Church work with young adults; Spiritual formation; Young adults -- Religious life